Asymmetric Hydrogenation of Isoquinolinium Salts Catalyzed by Chiral Iridium Complexes: Direct Synthesis for Optically Active 1, 2, 3, 4‐Tetrahydroisoquinolines1. Issue 7 (9th January 2013) - Iimuro, Atsuhiro; Yamaji, Kenta; Kandula, Sathaiah; Nagano, Takuto; Kita, Yusuke; Mashima, Kazushi
<x xml:space="preserve">Abstract</x> The salt makes the difference: In the presence of a chiral iridium catalyst, 1‐ and 3‐substituted as well as 1, 3‐disubstituted isoquinolinium salts can be hydrogenated, giving the corresponding 1, 2, 3, 4‐tetrahydroisoquinolines in high enantiomeric excess after a basic workup (see scheme). This protocol is applicable to the synthesis of the prescription drug solifenacin.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>